Fluticasone/formoterol dry powder versus budesonide/formoterol in adults and adolescents with uncontrolled or partly controlled asthma - Cukier, Alberto (2016)
This 12-week study compared the efficacy and safety of a fixed combination of fluticasone propionate plus formoterol (FL/F) 250/12 mu g b.i.d. administered via a dry powder inhaler (DPI) (Libbs Farmaceutica, Brazil) to a combination of budesonide plus formoterol (BD/F) 400/12 mu g b.i.d. After a 2-week run-in period (in which all patients were treated exclusively with budesonide plus formoterol), patients aged 12-65 years of age (N = 196) with uncontrolled asthma were randomized into an actively-controlled, open-labeled, parallel-group, multicentre, phase III study. the primary objective was to demonstrate non-inferiority, measured by morning peak expiratory flow (mPEF).The non-inferiority was demonstrated. A statistically significant improvement from baseline was observed in both groups in terms of lung function, asthma control, and the use of rescue medication. FL/F demonstrated a statistical superiority to BD/F in terms of lung function (FEV1) (p = 0.01) and for asthma control (p = 0.02). Non-significant between-group differences were observed with regards to exacerbation rates and adverse events.In uncontrolled or partly controlled asthma patients, the use of a combination of fluticasone propionate plus formoterol via DPI for 12-weeks was non-inferior and showed improvements in FEV1 and asthma control when compared to a combination of budesonide plus formoterol. (Clinical Trial number: ISRCTN60408425). (C) 2013 Elsevier B.V. All rights reserved.